Genetics of Simple Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
A clinical and genetic study of three families with simple febrile seizures (FS) and an autosomal dominant (AD) trait with high penetrance is reported from the Hopital Pitie-Salpetriere, Paris, France.